Why low-carbon technological innovation hardly promote energy efficiency of China? – Based on spatial econometric method and machine learning. (October 2021) - Li, Wenchao; Xu, Jian; Ostic, Dragana; Yang, Jialiang; Guan, Rongdi; Zhu, Lin
Highlights: China's energy efficiency is heterogeneous in spatial distribution. Different heterogeneous level of energy efficiency are tested. Agglomeration of innovation resources makes the raise of energy efficiency uncertain. Balanced innovation resource allocation is necessary. Abstract: Can low-carbon technological innovation improve energy efficiency in China? Despite China's attempts to improve energy efficiency through low-carbon technological innovation for several years, many scholars argue that innovation does not necessarily produce the expected outcomes. This study tests the heterogeneity of energy efficiency in China based on Data Envelopment Analysis (DEA) and machine learning and demonstrates the spatial spillover effect of regional agglomeration of low-carbon technology innovation on energy efficiency using the dynamic spatial Durbin model (DSDM). The results show that: (a) China's energy efficiency is heterogeneous in spatial distribution, and it has the characteristics of spilling over from the east to the central and western regions. (b) The direct effect of low-carbon technological innovation on energy efficiency is positive, but the indirect effect is negative, and the total effect is negative. The low-carbon technological innovation has an agglomeration effect, i.e., innovation resources tend to gather in higher energy efficiency regions. (c) Government influence, industrial structure, and foreign capital are key factors of low-carbon technology innovation. Based on these results, this study suggests the following policy recommendations: Narrow the low-carbon technology innovation gap between the developed and developing regions; promote the utilization efficiency of low-carbon technology innovation resources; open the low-carbon technological innovation to foreign investment and encourage low-carbon enterprises to cooperate with them.